On the polar nature and invariance properties of a thermomechanical theory for continuum-on-continuum homogenization. (November 2021) - Mandadapu, Kranthi K; Abali, B Emek; Papadopoulos, Panayiotis
This paper makes a rigorous case for considering the continuum derived by the homogenization of extensive quantities as a polar medium in which the balances of angular momentum and energy contain contributions due to body couples and couple stresses defined in terms of the underlying microscopic state. The paper also addresses the question of invariance of macroscopic stress and heat flux and form-invariance of the macroscopic balance laws.